Early recurrence of pancreatic cancer after resection and during adjuvant chemotherapy - Richard Fischer; Matthias Breidert; Tobias Keck; Frank Makowiec; Christian Lohrmann; Jan Harder (The Saudi Journal of Gastroenterology, 2012)
Background/Aim: Adjuvant chemotherapy for 6 months is the current standard of care after potentially curative resection of pancreatic cancer and yields an overall survival of 15-20 months. Early tumor recurrence before or during adjuvant chemotherapy has not been evaluated so far. These patients may not benefit from adjuvant treatment. Patients and Methods: Thirty-five patients with resection of ductal pancreatic carcinoma and adjuvant chemotherapy with gemcitabine were analyzed between 2005 and 2007. All patients had a computed tomography (CT) scan before and during adjuvant chemotherapy after 2-3 months, 12/35 patients had a histologically confirmed R1 resection. Recurrence of pancreatic cancer was determined by CT scan and the clinical course. Results: Median survival of 35 patients with resected pancreatic cancer was 19.7 months, and the 2-year survival was 44%. Thirteen (37%) of the 35 patients analyzed with a CT scan showed tumor recurrence during adjuvant chemotherapy. Overall survival of patients with tumor recurrence was 9.3 months with a 2-year survival rate of 13%, whereas median overall survival of patients without early relapse was 26.3 months (P<0.001). Local recurrence of pancreatic cancer occurred in 38% (5/13); 46% (6/13) of patients developed distant metastasis, and 38% (5/13) developed lymph node metastasis. Early tumor recurrence during or adjuvant chemotherapy did not correlate with R status (R1 vs R0, P=0.69), whereas histologically confirmed lymph node invasion (pN0 vs pN1) and grading showed a statistically significant correlation with early relapse (P<0.05). Conclusion: A significant fraction of patients with resected pancreatic cancer have early relapse during adjuvant chemotherapy, especially those with lymph node metastasis. Radiologic examinations prior to and during adjuvant chemotherapy will help to identify patients with tumor recurrence who are unlikely to benefit from adjuvant treatment and will need individualized palliative chemotherapy.